Graphene and transition metal dichalcogenide nanosheets as charge transport layers for solution processed solar cells. Issue 10 (December 2016) - Balis, Nikolaos; Stratakis, Emmanuel; Kymakis, Emmanuel
Abstract : This review focuses on the recent progress and critical aspects of the utilization of solution processable graphene oxide (GO) and graphene-like transition metal dichalcogenides (TMDs) nanosheets as either the hole or the electron transport extraction layer in solution processed solar cells (SPSCs), including organic, dye-sensitized, quantum dot and perovskite solar cells. GO and TMDs are becoming very attractive due to their solution processability and more importantly due to their tunable electronic structure via proper functionalization routes, which in effect can optimize the charge transport process to the collection electrodes. Challenges and future applications of these materials in large area SPSCs, as well as the transition of the related technology from the laboratory scale to the industry will be analyzed and discussed.